Direct Torque Control Strategy of PMSM Employing Ultra Sparse Matrix Converter - Muldi Yuhendri; Ahyanuardi Ahyanuardi; Aswardi Aswardi (International Journal of Power Electronics and Drive Systems (IJPEDS), 2018)
Matrix converter is a good choice for Permanent Magnet Synchronous Motor (PMSM) drives, because it has high power density and does not require dc-link energy storage. the disadvantages of conventional matrix converter is using 18 active switches, so it becomes expensive and the modulation method becomes more complicated than back to back converter. To minimize this problem, this paper proposes variable speed drive of PMSM using Ultra Sparse Matrix Converter (USMC) based on Direct Torque Control (DTC) methods. This converter uses only 9 active switches, making it cheaper than conventional matrix converter. DTC is designed based on Space Vector Modulation (SVM) to reduce torque and flux ripples due to  the hysteresis control in conventional DTC. The simulation results show that DTC based SVM using USMC effectively controls the rotor speed with low torque and flux ripples.